Komitmen Organisasional Dan Kepuasan Kerja Dampaknya Terhadap Kinerja Karyawan Di Dinas Kependudukan Dan Pencatatan Sipil Kota Malang - Ismy Dahlia Safitri; Nur Hidayati; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims the effect of organizational commitment and job satisfaction on employee performance at the Department of Population and Civil Registration of Malang City in 2021. The population in this study were all employees of the Department of Population and Civil Registration of Malang City in 2021 with a total of 146 employees. Sampling technique using purposive sampling method obtained a sample of 76 employees. The method of data collection in this study used the method of distributing questionnaires and documentation. The data analysis technique used multiple linear regression with SPSS version 26. The results showed that organizational commitment and job satisfaction had a positive and significant effect on employee performance.Keywords: organizational commitment, job satisfaction, employee performance